소아 근시 환자에서 각막굴절교정렌즈와 싸이클로펜톨레이트의 근시억제 효과에 대한 비교 연구 - 김다란(Da Ran Kim); 박선경(Sun-Kyoung Park); 나경선(Kyung Sun Na); 박미라(Mi Ra Park) (Daihan angwa haghoi jabji, 2022)
목적: 소아 근시 환자에서 각막굴절교정렌즈(orthokeratology lens, Ortho‐K 렌즈)와 싸이클로펜톨레이트(cyclopentolate)의 근시억제효과를 비교해보고자 하였다. 대상과 방법: 본 연구는 양안에 Ortho‐K 렌즈를 적용한 36명, 싸이클로펜톨레이트를 점안한 28명의 소아 근시 환자의 우안을 대상으로 총 64안의 의무기록을 후향적으로 분석하여 임상 결과를 비교하였다. 성별, 나이, 첫 개입을 시작한 나이, 관찰 기간을 조사하였다. 시력 및 첫 개입 당시, 6개월, 12개월, 24개월째의 안축장을 측정하여 비교하였다. 결과: 2년 추적 관찰 후 Ortho‐K 렌즈군에서 기저 안축장(baseline axial length [AL])에 대한 시간에 따른 안축장 변화(AL change, △AL)는 12개월째 0.3 ± 0.25 mm, 24개월째 0.52 ± 0.34 mm로 통계적으로 유의하게 감소하였으며(p for trend ＜0.001), 싸이클로펜톨레이트군에서도 12개월째 0.36 ± 0.17 mm, 24개월째 0.62 ± 0.29 mm로 시간에 따라 안축장의 변화가 유의하게 감소하였다(p for trend=0.022). 두 군 간의 근시 조절 효과를 비교해보았을 때 Ortho‐K 렌즈군이 싸이클로펜톨레이트군에 비해 시간에 따른안축장 변화가 통계적으로 유의하게 더 적었다(p=0.038). 결론: Ortho‐K 렌즈는 근시 진행을 효과적으로 억제할 수 있으며, 싸이클로펜톨레이트는 Ortho‐K 렌즈에 비해 소아 근시억제 효과가유의하게 적었다. Purpose: To compare the effects of orthokeratology lens (Ortho‐K lens) and topical cyclopentolate on myopia progression in children. Methods: This retrospective study analyzed the medical records of 36 children who received Ortho‐K lens and 28 who received cyclopentolate (i.e., total of 64 eyes). The following data were recorded: sex, age, age at first intervention, follow‐up duration, and visual acuity and axial length (AL) at the time of first treatment and after 6, 12, and 24 months of treatment. Results: In the Ortho‐K group, the changes of AL significantly decreased by 0.3 ± 0.25 mm at 12 months and 0.52 ± 0.34 mm at 24 months (p for trend < 0.001). In the cyclopentolate group, the changes of AL significantly decreased by 0.36 ± 0.17 mm at 12 months and 0.62 ± 0.29 mm at 24 months (p for trend = 0.022). Compared to the use of cyclopentolate, the use of Ortho‐K lens resulted in smaller changes in AL during follow‐up (p = 0.038). Conclusions: In myopic children, Ortho‐K reduced myopia progression, whereas cyclopentolate significantly less affect myopia progression than Ortho‐K lens. KCI Citation Count: 0